Трансдисциплинарность в контексте традиции философского знания - Дольская, Ольга Алексеевна (Національний педагогічний університет ім. М. П. Драгоманова, Українська академія наук, 2012)
Трансдисциплинарность рассматривается как один из принципов в организации режима получения нового знания. Анализируются ее эпистемологическая и экзистенциальная составляющие.

Transdisciplinary is considered as one of principles in organization of the mode of receipt of a new knowledge. It is analysed her epistemology and existential components.
Phenomenon of Transdisciplinary in the context of tradition of philosophical knowledge
Keywords: трандисциплинарность; производство знания; эпистемология; проблема рациональности; трансцендентный опыт; повседневный опыт; Transdisciplinary; production of knowledge; epistemology; problem of rationality; transcendent experience; everyday’s experience